Learning to Sing Indonesia Raya Songs to Cultivate the Character of Love for the Motherland in Grade 1 Students of Ngijo 01 Elementary School, Semarang City - Tasya Muharima Istawa; Putri Yanuarita Sutikno (Journal of Educational Sciences, 2026)
Despite the strong emphasis on character education in primary schools, empirical studies examining practical classroom-based strategies for cultivating patriotic values among early-grade students remain limited. In many schools, the singing of the Indonesian national anthem Indonesia Raya is commonly practiced as a ceremonial routine rather than as a structured pedagogical activity. This study aims to examine how the habituation of singing Indonesia Raya can function as a learning strategy to foster the character of love for the motherland among Grade 1 students at SD Negeri Ngijo 01 Semarang. A qualitative case study design was employed involving twenty-four students, one classroom teacher, and the school principal. Data were collected through classroom observations, semi-structured interviews, and documentation, and analyzed through coding, behavioral categorization, and thematic interpretation. The findings show that 70.83% of students demonstrated disciplined participation within the Maxi and Consistent categories, while 29.17% were categorized as Developing and Intervention, indicating the need for additional pedagogical reinforcement. These findings suggest that structured musical habituation, supported by teacher modeling and contextual explanations, can facilitate the gradual internalization of patriotic character among early elementary students.